BODY COMPOSITION OF ADULTS IN MARINGÁ, PARANÁ – BRAZIL. (Fiep Bulletin - online, 2011)
Body composition is considered one of the components of physical fitness because of its association with the level of body fat and metabolic changes. Thus, the most common way to assess nutritional status and its association with body fat is through BMI and Fat Percentage. The objective of this study was to evaluate the body composition profile of adults in the city of Maringa. The research was a descriptive study conducted in the city of Maringa-PR, which evaluated 709 adults, 544 women and 165 men. The statistical analyses involved the Chi-square (X²) and Man – Whitney tests. It was found that most women (46.88%) and men (45.45%) are in normal ranges. While 18.93% and 14.55% of women men fall into the category obesity. These findings when compared to studies in other brazilian regions had similar rates of overweight and obesity in male and female populations.It was also found that most women find themselves with the fat percentage "very high" (45.03%) and most men are evaluated with values described as "above average" (37.57%). The results indicate the importance of using bioimpedance in population studies for diagnosis of obesity.
Keywords: Obesity; Overweight and Bioimpedance